2002
DOI: 10.1128/aem.68.7.3183-3189.2002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Listeria monocytogenes Scott A Isolate with High Tolerance towards High Hydrostatic Pressure

Abstract: An isolate of L. monocytogenes Scott A that is tolerant to high hydrostatic pressure (HHP), named AK01, was isolated upon a single pressurization treatment of 400 MPa for 20 min and was further characterized. The survival of exponential-and stationary-phase cells of AK01 in ACES [N-(2-acetamido)-2-aminoethanesulfonic acid] buffer was at least 2 log units higher than that of the wild type over a broad range of pressures (150 to 500 MPa), while both strains showed higher HHP tolerance (piezotolerance) in the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
107
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 22 publications
6
107
0
Order By: Relevance
“…Interestingly, some studies observed a correlation between heat and pressure resistance among natural isolates of E. coli (1,4). Other studies, in which HHP-resistant mutants of E. coli (16) and of L. monocytogenes (27) were isolated after selection, also found that HHP resistance coincided with increased heat resistance. In E. coli O157:H7, the natural variation in pressure resistance was suggested to be correlated to the activity of the stationary-phase sigma factor (47).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Interestingly, some studies observed a correlation between heat and pressure resistance among natural isolates of E. coli (1,4). Other studies, in which HHP-resistant mutants of E. coli (16) and of L. monocytogenes (27) were isolated after selection, also found that HHP resistance coincided with increased heat resistance. In E. coli O157:H7, the natural variation in pressure resistance was suggested to be correlated to the activity of the stationary-phase sigma factor (47).…”
Section: Discussionmentioning
confidence: 82%
“…Most in vivo observations on living cells exposed to HHP can be linked to these two effects: inhibition of key enzymes (43,49); and inactivation of cellular structures and processes, including transcription (9), ribosomes (39), microtubules (33) and membrane proteins (46), and structural and functional disruption of the cell membrane (11,42). Remarkable differences exist in the pressure sensitivity among bacterial species and even strains (1,4), and several groups have reported the isolation of mutants with acquired HHP resistance (12,16,27). The bacterial response to high pressure has been studied mainly in deep-sea bacteria (20,21,29,30,59).…”
mentioning
confidence: 99%
“…Some studies have found a correlation between heat and high-pressure resistance among natural isolates of E. coli 21) and mutant isolates of E. coli and Listeria monocytogenes screened after highpressure treatment. 33,34) Membrane damage is one of the main causes of high-pressure induced cell death, but the nature of the damage and its relation to cell death differ among species and phases of growth. 35) Using a promoterless alkaline phosphatase as a reporter of oxidative stress, high hydrostatic pressure was found to be analogous to cytoplasmic oxidative stress in E. coli.…”
Section: Recent Advanced Studies Of the Effects Of High Pressurementioning
confidence: 99%
“…This is a novel, unexpected finding, since CtsR inactivation generally causes derepression of heat stress genes, thus rendering cells more prepared to face stressful conditions. Indeed, in most Grampositive bacteria analyzed so far, ctsR mutations increased heat resistance and/or general stress tolerance (4,16,17,18,24,36). The cell morphology of wild-type L. plantarum and ⌬ctsR mutant strains was analyzed before and after heat stress exposure by scanning electron microscopy (SEM) (Fig.…”
mentioning
confidence: 99%